Pretargeted Positron Emission Tomography Imaging That Employs Supramolecular Nanoparticles with in Vivo Bioorthogonal Chemistry - Hou, Shuang (ACS Nano, 2016)
A pretargeted oncologic positron emission tomography (PET) imaging that leverages the power of supramolecular nanoparticles with in vivo bioorthogonal chemistry was demonstrated for the clinically relevant problem of tumor imaging. The advantages of this approach are that (i) the pharmacokinetics (PKs) of tumor-targeting and imaging agents can be independently altered via chemical alteration to achieve the desired in vivo performance and (ii) the interplay between the two PKs and other controllable variables confers a second layer of control toward improved PET imaging. In brief, we utilized supramolecular chemistry to synthesize tumor-targeting nanoparticles containing transcyclooctene (TCO, a bioorthogonal reactive motif), called TCO⊂SNPs. After the intravenous injection and subsequent concentration of the TCO⊂SNPs in the tumors of living mice, a small molecule containing both the complementary bioorthogonal motif (tetrazine, Tz) and a positron-emitting radioisotope ((64)Cu) was injected to react selectively and irreversibly to TCO. High-contrast PET imaging of the tumor mass was accomplished after the rapid clearance of the unreacted (64)Cu-Tz probe. Our nanoparticle approach encompasses a wider gamut of tumor types due to the use of EPR effects, which is a universal phenomenon for most solid tumors.